2020
DOI: 10.1155/2020/1487609
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Circular RNA ciRS-7 in Various Cancers: A PRISMA-Compliant Meta-Analysis

Abstract: Background. Circular RNAs (circRNAs) have been shown to be involved in tumorigenesis. As a member of circRNAs, ciRS-7 is thought to be a negative prognostic indicator in multiple types of cancer. The present study aimed to comprehensively explore the value of ciRS-7 in tumor malignancy. Materials and Methods. A systematic review of PubMed, Web of Science, and the Cochrane library was carried out to examine the related studies. The pooled odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Yuan et al claimed that circRNAs might serve as potential biomarkers for colorectal cancer [ 24 ]. In addition, 2 independent meta-analyses suggested that circRNA CDR1as could act as diagnostic and prognostic biomarkers in various malignant tumors [ 10 , 25 ]. Exploring the value of circRNAs as biomarkers will provide promising guidance for clinical decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al claimed that circRNAs might serve as potential biomarkers for colorectal cancer [ 24 ]. In addition, 2 independent meta-analyses suggested that circRNA CDR1as could act as diagnostic and prognostic biomarkers in various malignant tumors [ 10 , 25 ]. Exploring the value of circRNAs as biomarkers will provide promising guidance for clinical decision.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, circRNAs can be used as diagnostic and prognostic markers for malignant tumors [ 8 , 9 ]. Previous meta-analyses have verified the prognostic values of ciRS-7 [ 10 ] and circHIPK3 [ 11 ] in malignant tumor patients.…”
Section: Introductionmentioning
confidence: 97%
“…Its predictive value in diagnosis and prognosis for malignancy has been gradually explored. Several circRNAs have been certified to be associated with the development and progression of various tumors, such as ciRs-7 [ 34 ]. The predictive role of circRNA in different malignancies, including lung cancer, colorectal cancer, and laryngeal cancer, has also been reported recently [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that CDR1as is expressed abnormally in many cancer types (Pan et al, 2018;Su et al, 2018;Tanaka et al, 2019;Lin et al, 2020;Tian et al, 2020;Zhou et al, 2020). The expression of CDR1as is upregulated in most tumors, such as colorectal cancer, hepatocellular carcinoma and breast cancer, and it exerts a tumor-promoting effect (Tang et al, 2017;Weng et al, 2017;Xu et al, 2017;Yuan et al, 2019;Zhang Z. et al, 2020;Zhao Y. H. et al, 2020).…”
Section: The Expression Of Cdr1as In Cancermentioning
confidence: 99%